Asertividad y productividad del personal de ventas en la empresa Multiventas Giovanna, Iquitos 2023 - Muro del Aguila, Kevinn Martin (2024)
The purpose of this study is to identify the type and strength of association that exists between the assertiveness and productivity of the sales staff of a commercial company in the city of Iquitos in 2024. To this end, a non experimental and transversal research was designed; using the survey technique and a structured questionnaire as a data collection instrument. The population is made up of the 26 workers who make up the sales force of the company under study. The main hypothesis is that there is a positive and significant relationship between the variables under study, which, when tested through the Pearson coefficient, yielded a value of 0.294, which proves the hypothesis in the sense that, Yes, there is a positive correlation of a “weak” degree, so it can be stated that, the greater the assertiveness, the better the productivity. At a descriptive level, it was revealed that the majority of workers have a high level of assertiveness (42.31%) and the productivity of most of them is very high (38.46%). It is recommended that company managers arrange for the implementation of a training plan to increase the assertiveness of their sales force; as well as, the allocation of sales quotas is reviewed.